Analysis of the impact of the classification of the market risk brazilian credit - JoÃo Henrique Lemos Costa (2009)
In this article, we analyze the rating impact on credit volume and the long-run equilibrium relationship between Gross Domestic Product (GDP), deposits and credit for the most relevant player in Brazilian financial system, under the monetary structural framework developed by Bernanke and Blinder (1988), which models the credit supply as a function of some idiosyncratic and macroeconomic key-variables. The results obtained from linear regressions and from an error-correction Engle and Ganger (1987) approach enables us to evidence the credit channel relevance as a monetary policy transmission instrument, emphasizing the relevance in observing the bank assets rubric. Based on the well-succeed benchmark model performance, we are able to measure the positive and significant impact of the investment grade, according to MoodyÂs agency, while intermediary rating changes do not seem to be so relevant. We also have evidences about the insignificant impact of interest rate changes on GDP growth rate.